Curtailing capture through the European banking union: A note of caution - Cornelia Woll (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
One of the motivations for establishing a European banking union was the desire to break the ties with between national regulators and domestic financial institutions in order to prevent regulatory capture. However, supervisory authority over the financial sector at the national level can also have valuable public benefits. The aim of this policy letter is to detail these public benefits in order to counter discussions that focus only on conflicts of interest. It is informed by an analysis of how financial institutions interacted with policy-makers in the design of national bank rescue schemes in response to the banking crisis of 2008. Using this information, it discusses the possible benefits of close cooperation between financial institutions and regulators and analyzes these in the wake of a European banking union.
urn:nbn:de:hebis:30:3-341018
Keywords: 330; public-private relations; capture; collective action; social relations